Pediatric Theranostics in a 13-Year-Old Female with Bronchial Carcinoid - Trpezanovski, Justine; Karpelowsky, Jonathan; Hesketh, Elizabeth; London, Kevin (World Journal of Nuclear Medicine, 2025)
Pediatric bronchial carcinoid tumors are rare, accounting for a significant proportion of primary lung tumors in children but only a small fraction in adults. These tumors can present with symptoms such as cushing's syndrome due to ACTH secretion. Complete surgical resection typically results in favorable outcomes, with most tumors expressing somatostatin receptors, making them amenable to peptide receptor radionuclide therapy (PRRT) with (177Lu)Lu-DOTA-TATE (LuTATE).This case report describes a 13-year-old female with a bronchial carcinoid tumor treated with multi-cycle high-dose LuTATE therapy in the neoadjuvant setting. Initial imaging and biopsy confirmed a grade G1 pulmonary carcinoid with intense somatostatin receptor expression. The patient underwent two cycles of LuTATE, with dosimetry calculations guiding dose escalation while maintaining safe kidney radiation exposure. Posttherapy scans showed a significant metabolic response of suspected nodal metastases and evidence of partial response of the primary tumor.Two further LuTATE cycles were administered, with continued monitoring of kidney dosimetry to ensure safety. The treatment was well-tolerated, and the patient showed no significant complications. The case highlights the potential of LuTATE therapy to downstage tumors and reduce surgical morbidity in pediatric patients. Given the rarity of pediatric bronchial carcinoid tumors, phase III clinical trials are unlikely, but this report supports the inclusion of LuTATE in multidisciplinary treatment planning.In conclusion, LuTATE therapy, guided by dosimetry calculations, offers a valid treatment option for pediatric bronchial carcinoid tumors, balancing efficacy, and safety in a challenging clinical scenario.
Keywords: bronchial; carcinoid; LuTATE; neuroendocrine; pediatrics